Front-of-Pack Food Labelling and Legal Iconography: An Example of Legal Transplant and the New Latin American Paradigm - Ferrante, Alfredo (2021)
This paper analyzes the front-of-pack food labelling, with particular attention to Chilean, Colombian, Ecuadorian and Peruvian regulations (also de lege ferenda regulations). The aim is to contribute to a better understanding and use a comparative methodology, in particular of the figure of the legal transplant. In that sense, a concrete example of operability (not necessarily achieved) of a transplant is provided. The work also shows that the analyzedlegislations are far from European models and take Latin American standards as a reference, contributing to a paradigm shift in relation to the traditionalinfluence of foreign regulations that is usually incorporated into Latin American national systems.